EVALUASI PROGRAM PENGEMBANGAN PARIWISATA GEOPARK SILOKEK (STUDI PADA DINAS PARIWISATA PEMUDA DAN OLAHRAGA KABUPATEN SIJUNJUNG SUMATERA BARAT) - Anggit Ganang Pratikto; , Ari Subowo; Teuku Afrizal (Journal of Public Policy and Management Review, 2022)
The tourism development program at the Silokek Geopark carried out by DISPARPORA is a form of effort to be independent, empower and take advantage of the potential that exists in the Silokek Geopark area. This study aims to provide an overview of the evaluation of the study and explain the influencing factors in the tourism development program carried out by the Youth and Sports Tourism Office of Sijunjung Regency at Geopark Silokek. This study uses descriptive qualitative research methods, data collection is done by observation, interviews and documentation. The results showed that the tourism development program carried out by DISPARPORA was good but the evaluation that had been carried out by evaluating the program evaluation, evaluating the difficulties or obstacles to program implementation, and evaluating the impact of the program found that the community's economic improvement statements from the community and the real situation were not on target. There are factors that influence the tourism development program at Geopark Silokek, the driving factors are the abundant natural resources of Sijunjung Regency, the support from the government and collaboration from DISPARPORA with stakeholders. While the inhibiting factors such as the people there are an agrarian society whose mindset must be changed to tourism, the land there is the customary land of the people so that it makes it difficult to permit regional development, Furthermore, there are problems with budgeting, access to facilities and infrastructure and do not yet have a clear target market.